Three-dimensional Participatory Mapping for Fire Disaster Risk Reduction in Batulaya Village: Pemetaan Partisipatif Tiga Dimensi untuk Pengurangan Risiko Bencana Kebakaran di Desa Batulaya - Adyla, Nur; Priadmodjo, Anggit; Astinawaty, Astinawaty; Syamsiar, Nur Ratika; Tasrif, Ali Akbar; Erwin, Muh Alfa Rezi (Universitas Lancang Kuning, 2025)
This service aims to reduce disaster risk in Batulaya Village through participatory mapping of threats, vulnerabilities and risks using three-dimensional media. Observation, participatory, and data analysis methods are used to obtain detailed information and in accordance with the condition of resources and carrying capacity in disaster mitigation steps. The results of this community service show that Batulaya Village is vulnerable to disasters, especially fires, and the community is less prepared to face disasters. Through participatory mapping, the integration of local knowledge and scientific methods can help reduce disaster risk. The results of this mapping activity can later be used as a basis for further disaster risk reduction efforts.